Long-term effect of mobile phone-based education and influencing factors of willingness to receive HPV vaccination among female freshmen in Shanxi Province, China - Liying Sun; Jingjing Hu; Huihui Gao; Sunyi Wang; Binghan Wang; Jiawen Wang; Hui Li; Jianbing Wang; Changzheng Yuan; Xi Zhang (Taylor & Francis Group, 2022)
Background This study was conducted to characterize the long-term effect of mobile-based education on Chinese female freshmen and disclose the possible predictors of their willingness to get vaccinated based on the information-motivation-behavioral skills (IMB) model. Methods We randomly assigned 509 participants to a 7-day mobile-based educational intervention or control group and collected information about general information, health, and sexual behavior, HPV vaccination intention and action, HPV-related knowledge, cognition, and behavioral skill by an online self-administrated questionnaire at baseline, post-intervention, and at the 1-month and 3-month follow-ups. Results The intervention arm showed an improvement in IMB scores after education. Despite the persistent improvement in knowledge, the improvement in their motivation and behavioral skills decreased at the 1-month and 3-month follow-ups. Participants' vaccination willingness was elevated after the baseline survey in both the intervention and control groups, while the overall appointment/vaccination rate was only 3.73% 3 months later. The intention to get vaccinated was associated with knowing HPV (adjusted OR: 2.37, 95% CI: 1.44 - 3.89), perceiving more barriers (adjusted OR: 2.16, 95% CI: 1.44 - 3.25), higher subjective norms (adjusted OR: 2.05, 95% CI: 1.26 - 3.32), and having more behavioral skills (adjusted OR: 2.95, 95% CI: 1.79 - 4.87). Conclusion Seven-day mobile-based education was effective to increase IMB model scores among female freshmen. However, the improvement in motivation and behavioral skills was not persistent. Information, perceived barriers, subjective norms, and behavioral skills were discovered to be influencing factors of vaccination intention. Future research with longer, more convenient, and more tailored education to the main influencing factors is warranted.